Prophylactic pegfilgrastim reduces febrile neutropenia in ramucirumab plus docetaxel after chemoimmunotherapy in advanced NSCLC: post hoc analysis from NEJ051 - Keita Miura; Ou Yamaguchi; Keita Mori; Atsushi Nakamura; Motohiro Tamiya; Tomohiro Oba; Noriko Yanagitani; Hideaki Mizutani; Takashi Ninomiya; Tomosue Kajiwara; Kentaro Ito; Akihiko Miyanaga; et al. (Scientific Reports, 2024)
Abstract Ramucirumab plus docetaxel (RD) can cause febrile neutropenia (FN), which frequently requires the prophylactic administration of pegfilgrastim. However, the effects of prophylactic pegfilgrastim on FN prevention, therapeutic efficacy, and prognosis after RD have not been fully evaluated in patients with advanced non-small-cell lung cancer (NSCLC). Two hundred and eighty-eight patients with advanced NSCLC who received RD as second-line therapy after platinum-based chemotherapy plus PD-1 blockade were included. Patients were divided into groups with and without prophylactic pegfilgrastim, and adverse events, efficacy, and prognosis were compared between both groups. Of the 288 patients, 247 received prophylactic pegfilgrastim and 41 did not. The frequency of grade 3/4 neutropenia was 62 patients (25.1%) in the pegfilgrastim group and 28 (68.3%) in the control group (p < 0.001). The frequency of FN was 25 patients (10.1%) in the pegfilgrastim group and 10 (24.4%) in the control group (p = 0.018). The objective response rate was 31.2% and 14.6% in the pegfilgrastim and control groups (p = 0.039), respectively. The disease control rate was 72.9% in the pegfilgrastim group and 51.2% in the control group (p = 0.009). Median progression free survival was 4.3 months in the pegfilgrastim group and 2.5 months in the control group (p = 0.002). The median overall survival was 12.8 and 8.1 months in the pegfilgrastim and control groups (p = 0.004), respectively. Prophylactic pegfilgrastim for RD reduced the frequency of grade 3/4 neutropenia and febrile neutropenia and did not appear to be detrimental to patient outcome RD. Clinical Trial Registration Number: UMIN000042333.